Pengaruh Iklim Sekolah Dan Kedisiplinan Terhadap Prestasi Belajar Siswa - ., Salma (Eklektika, 2013)
The study aims to examining, school climat, student discipline toward learning achievement in classes XI Students at Public Vocational School (SMKN) 1 Jeneponto. This type of the studyÂ  a descriptive research, which categorized as quantitative research. The quantitative is meant to test hypotheses and operation of variable. The variables consists of three variables : namely school climate (X1) students discipline (X2), as independent variable, and student achievement as the dependent variable.The population of the study was grade XI at SMKN Jeneponto academic year 2011/2012 whit the total number 420 students. The samples were selected by using simple random sampling which obtainedÂ  126 students. Data wereÂ  collected troughÂ  questionnaire andÂ  documentation. Data were then analyzed by employing descriptive statistic andÂ  inferential statistics. The results of the study reveal that school climate is categorized as medium, studentsâ discipline of grade XI at SMK 1 Jeneponto is categorized as high, the and studentsâ learning achievement is categorized as fair. Other thanÂ  school climate, studentÂ  discipline gives influence toward students learning, achievement both individually and collaboratively. Keywords: School Climate Student Discipline and toward learning achievement.